2021
DOI: 10.3389/fcomp.2021.659600
|View full text |Cite
|
Sign up to set email alerts
|

A Canonical Set of Operations for Editing Dashboard Layouts in Virtual Reality

Abstract: Virtual reality (VR) is a powerful technological framework that can be considered as comprising any kind of device that allows for 3D environments to be simulated and interacted with via a digital interface. Depending on the specific technologies used, VR can allow users to experience a virtual world through their different senses, i.e., most often sight, but also through touch, hearing, and smell. In this paper, it is argued that a key impediment to the widespread adoption of VR technology today is the lack o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Numerous scientific studies have explored the benefits and comparative effectiveness of desktop virtual realities over classical computing interfaces in terms of reduction of mental strain [34] , [33] , enhanced memory retrieval [6] , [32] , [48] , [23] , [18] , [74] , [86] , [46] , improvement of digital guidance in workflows [88] , [87] and improved possibilities for content management [79] , [81] , [80] . However, few if any previous works have proposed a general theory as to how such benefits can be achieved in a systematic and dependable way.…”
Section: Basic Conceptsmentioning
confidence: 99%
“…Numerous scientific studies have explored the benefits and comparative effectiveness of desktop virtual realities over classical computing interfaces in terms of reduction of mental strain [34] , [33] , enhanced memory retrieval [6] , [32] , [48] , [23] , [18] , [74] , [86] , [46] , improvement of digital guidance in workflows [88] , [87] and improved possibilities for content management [79] , [81] , [80] . However, few if any previous works have proposed a general theory as to how such benefits can be achieved in a systematic and dependable way.…”
Section: Basic Conceptsmentioning
confidence: 99%
“…Using the Doing-When-Seeing paradigm, in [16] we proposed a novel method that includes a set of operators categorized as selection operators, addition operators, placement operators, manipulation operators, and persistence operators for the editing of 2D display panels and 2D content layouts in 3D virtual spaces. The specific states and commands within the workflow are shown in Figure 2.…”
Section: Example Applications Of Dws: Creating 2d Display Panels a Us...mentioning
confidence: 99%
“…Based on our experiments, we showed that the proposed method and the operators it includes were all found to be useful by users, and at the same time were sufficient for the re-creation of existing 2D content layouts. We reported on this experiment in detail in [16].…”
Section: B Experimental Validationmentioning
confidence: 99%
“…Numerous scientific studies have explored the benefits and comparative effectiveness of desktop virtual realities over classical computing interfaces in terms of reduction of mental strain [20,21], enhanced memory retrieval [22][23][24][25][26][27][28][29], improvement of digital guidance in workflows [30,31] and improved possibilities for content management [32][33][34].…”
Section: Advantages Of Desktop 3d Vr Over 2d User Interfacesmentioning
confidence: 99%